Keterampilan Dasar Melempar, Menangkap, Dan Memukul Bola Pada Siswa Kelas Iv SD Negeri Kebun Bunga 1 Banjarmasin - Muhammad Habibie; Ari Tri Fitrianto (Universitas Aisyah Pringsewu, 2023)
The purpose of this study was to find out how high the level of basic skills in throwing, catching, and hitting the ball in grade IV students of SD Negri 1 Kebun Bunga, Banjarmasin. Academic Year 2022/2023. The research method uses observation techniques and test techniques which are carried out practically, namely the practice of basic movement abilities with small ball games. Researchers observed children's activities in the learning process in cycles one and two. While the test results data obtained from tests conducted at the end of learning. The research procedure was carried out in accordance with the research put forward by (Widyatmoko, 2016)